2020
DOI: 10.3389/fonc.2020.598965
|View full text |Cite
|
Sign up to set email alerts
|

A Nomogram Predicts Individual Prognosis in Patients With Newly Diagnosed Glioblastoma by Integrating the Extent of Resection of Non-Enhancing Tumors

Abstract: BackgroundThe extent of resection of non-contrast enhancing tumors (EOR-NCEs) has been shown to be associated with prognosis in patients with newly diagnosed glioblastoma (nGBM). This study aimed to develop and independently validate a nomogram integrated with EOR-NCE to assess individual prognosis.MethodsData for this nomogram were based on 301 patients hospitalized for nGBM from October 2011 to April 2019 at the Beijing Tiantan Hospital, Capital Medical University. These patients were randomly divided into d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…This conclusion was further confirmed by the results of multivariate Cox regression analysis of KPS in seven studies (Figure 4). 8,9,[16][17][18][19][20] Fourth, radiomics signatures refer to high-throughput quantitative features extracted from radiological images that are potentially related to genetic features. By extracting a large number of features that cannot be identified with the naked eye, the heterogeneity of tumor lesions is quantitatively evaluated by image feature parameters, so as to provide an objective basis for disease diagnosis, treatment and prognosis judgment.…”
Section: F I G U R E 6 Forest Plots Of Molecular Features In Gbm Prog...mentioning
confidence: 99%
See 3 more Smart Citations
“…This conclusion was further confirmed by the results of multivariate Cox regression analysis of KPS in seven studies (Figure 4). 8,9,[16][17][18][19][20] Fourth, radiomics signatures refer to high-throughput quantitative features extracted from radiological images that are potentially related to genetic features. By extracting a large number of features that cannot be identified with the naked eye, the heterogeneity of tumor lesions is quantitatively evaluated by image feature parameters, so as to provide an objective basis for disease diagnosis, treatment and prognosis judgment.…”
Section: F I G U R E 6 Forest Plots Of Molecular Features In Gbm Prog...mentioning
confidence: 99%
“…10,16,17,20 Maximum safe surgical resection of contrastenhancing tumor areas is generally considered the main surgical treatment to prolong GBM survival, but some studies have shown that reducing non-contrast-enhancing tumor volume would be conducive to increased survival and should not be ignored in clinical practice. 29,30 Through a retrospective study of 301 GBM patients hospitalized in Beijing Tiantan Hospital of Capital Medical University, Zhang et al 8 found that the resection range of EOR-NCE (extent of resection of NCE) was related to the prognosis of patients with newly diagnosed glioblastoma (nGBM), and the EOR-NCE nomogram had better prediction ability compared with EOR-CE (extent of resection of CE) model. IDH enzymes consist of three isoforms, and are essential enzymes participating in glutamine metabolism, redox regulation and other major metabolic processes.…”
Section: Treatmentmentioning
confidence: 99%
See 2 more Smart Citations